Private solutions for infrastructure in Honduras - Public Private Infrastructure Advisory Facility; World Bank (The World Bank, 2003)
This book is designed to promote the development of infrastructure services in Honduras, with the aim of improving the country's competitiveness and contributing to poverty reduction. Its central argument is that Honduras needs a significant increase in private investment in infrastructure services, which should take place in a more competitive environment and be subject to an adequate legal and regulatory framework. The study details the progress to date in Honduran infrastructure sectors, identifying the principal problems that exist and outlining a strategy for their solution. It proposes a general set of principles that should guide the provision of infrastructure services. In addition, it recommends specific policies for each sector. The document's scope includes the following services: transportation, water and sanitation, electricity, and telecommunications